Independent directors’ composition on stock price risk with media coverage as a moderating variable in manufacturing companies listed on the indonesia stock exchange for the 2019-2022 period - Anjelisa Paulina Kristin Siregar; Zuwina Miraza; Hafriz Rifki Hafas (Journal of Corporate Finance Management and Banking System, 2025)
The capital advertise for companies may be a implies to get capital from the more extensive community, so that there's an break even with dissemination of company proprietorship by the community and appears the openness of data from the company. This appears that the capital showcase could be a supporting instrument for the supportability of the economy in a nation. This research aims to analyze independent directors composition on stock price risk with media coverage as a moderating variable in Manufacturing Companies listed on the Indonesia Stock Exchange for the 2019- 2022 period. This research is an associative research. The population used in this study is Manufacturing Companies listed on the Indonesia Stock Exchange for the 2019-2022 period, totaling 195 companies. In this study, the sample used in this study was determined using a purposive sampling technique. The number of samples used in this study was 53 companies, with data observations of 53 companies x 4 years of research equal to 212 observation data. The analysis technique used is moderated regression analysis. The results of the study indicate that independent directors composition has a positive and significant effect on stock price risk in Manufacturing Companies listed on the Indonesia Stock Exchange for the 2019-2022 period. Media coverage does not moderate the effect of independent directors composition on stock price risk in Manufacturing Companies listed on the Indonesia Stock Exchange for the 2019-2022 period.